2017
DOI: 10.18502/kms.v2i1.793
|View full text |Cite
|
Sign up to set email alerts
|

Segregation in Porous NiTi Made by SHS in Flow Reactor

Abstract: The research considers the contribution of gases to the surface formation during self-propagating high-temperature synthesis (SHS) of porous titanium nickelide based alloys. The structure of the obtained porous alloys was analyzed using the methods of secondary ion mass spectrometry (SIMS), optical microscopy, scanning electron microscopy (SEM) and transmission electron microscopy (TEM).Nanocrystalline intermetallic oxycarbonitrides of a complicated structure were found on the porous titanium nickelide surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Depending on the SHS modes, porous materials with micro-and nano-sized pores can be produced. Studies made using mercury injection technique for measuring of pore size have shown that nano-sized pores, 1-100 nm, are also found in the alloy along with open pores [12].…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the SHS modes, porous materials with micro-and nano-sized pores can be produced. Studies made using mercury injection technique for measuring of pore size have shown that nano-sized pores, 1-100 nm, are also found in the alloy along with open pores [12].…”
Section: Resultsmentioning
confidence: 99%
“…The given shell comprises amorphous-nanocrystalline phases of intermetallic oxycarbonitrides in the form of epitaxial strata (foamy onlay and dense bisubstrate), as reported in References [20,21]. Considering the chemical composition and structure, the shell can be classified as a cermet Ti 4 Ni 2 (O,N,C) layer [42,43,44]. In fact, such amorphous-nanocrystalline phases are implied to exhibit high corrosion resistance.…”
Section: Fabrication Of Porous Shs Tinimentioning
confidence: 99%
“…Turning to the issue of the PTN enhanced corrosion resistance highlighted earlier, we were bound to note the superficial amorphous-nanocrystalline layer of intermetallic oxycarbonitrides, which entirely conceal the pore walls. It was denoted that the SHS process in itself is the rationale for this layer appearance resulting from retrograde gas streams interacting with the surface melt [43,54]. In our experience, we have studied the surface structures of high-porous PTN using a confocal laser scanning instrument [55].…”
Section: Characteristics Of Porous Shs Tinimentioning
confidence: 99%
See 2 more Smart Citations